LITERASI KESIAPSIAGAAN GEMPA DI SUMATERA BARAT: SEBUAH REVIEW - Rita Nasmirayanti; Rafki Imani; Meldia Fitri; Jihan Melasari; Maiyozzi Chairi; Nadra Arsyad (Construction and Material Journal, 2022)
The West Sumatra earthquake on September 30, 2009, has left a long sorrow for the families of the victims. The number of children who died at “Bimbel” center at that time was a proof of how vulnerable and at-risk children were to the threat of earthquakes. Learning from the past earthquakes, the local government and policy makers of West Sumatra Province have taken steps to take preventive measures, especially since the 2009 earthquake. Follow-up efforts such as reconstruction and rehabilitation have also been carried out well. However, these efforts will be meaningless if they are carried out sporadically and unsustainably. Efforts that have been carried out and have developed so far must be carried out from upstream to downstream in a more focused manner, starting from children to adults. Community capacity building, both through systematic socialization and sustainable disaster education, must continue to be carried out in every condition where there is no potential disaster in a disaster-prone area. The Law of the Republic of Indonesia No. 24 of 2007 concerning disasters, it is states that one of the groups of people who are vulnerable to disasters is the age group of children. Earthquake disaster education and knowledge need to be introduced early on. This study aims at evaluating the importance of literacy and disaster education for children. The method used is an evaluation method and a review of several previous studies, then summarize the results obtained from some of the previous studies. The results of the study stated that disaster literacy for children is important to do from an early age, so that they have more readiness and capacity to face disasters in the future. Keywords: Disaster Literacy, Disaster Education, Earthquake.